THE EXISTENCE OF ISLAMIC LAW COMPILATION ARTICLE 183 IN SOLVING INHERITANCE ISSUE OF MUSLIM COMMUNITIES IN MAKASSAR - Herawati, Andi (Al-Daulah : Journal of Criminal Law and State Administration Law, 2019)
The Qur'an and hadith of the Prophet are the main sources of Islamic law. The two sources can be understood and practiced based on their textual and contextual aspects, as well as being developed in detail by mujtahid scholars by paying attention to space and time with the situations and conditions in which they ijtihad resulting in the Compilation of Islamic Law. One of the contents of Islamic Law Compilation is the rule about the transfer of inheritance property to his surviving heirs. With the existence of these rules, the practice of distributing inheritance to Muslim communities, especially in the city of Makassar, varies greatly. There are by way of grants, deliberation, approaches to Islamic inheritance law, and also by mediation initiated by religious courts.The finding shows that the Muslim community in Makassar City is more likely to apply Compilation of Islamic Law article 183 because the article is strengthened by QS Ali Imra>n/3: 159 and QS al-Shura>/42: 38, which emphasize the importance of deliberation to reach agreement. The agreement was reached well and peacefully based on the instructions in article 183 Islamic Law Compilation by deliberating with all heirs, describing all inheritance properties both location and area, explaining the part of each heirs based on inheritance rules, agreeing on the distribution method used, and making and signing up a statement of agreement and witnessed. So thus, harmony, peace, and benefit can be created among families in particular and among the community in general.